Three-dimensional initial boundary-value problem of the convection of a viscous weakly compressible fluid. I. Global solvability - Moseenkov, V. B. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using asymptotic methods, we study the three-dimensional initial boundary-value problem of the convection of a viscous thermally inhomogeneous weakly compressible fluid which fills a cavity in a solid body. A theorem about the global solvability of this problem (with respect to time) is proved. For solving this problem, we suggest a convergent iteration process of a special form.